Uninterrupted oral anticoagulant therapy in patients undergoing unplanned percutaneous coronary intervention. (25th November 2020) - Venetsanos, D; Skibniewski, M; Janzon, M; Lawesson, S; Henareh, L; Bohm, F; Andell, P; Karlson, L; Simonsson, M; Erlinge, D; Omerovic, E; Alfredsson, J
Abstract: Background: To investigate the optimal periprocedural antithrombotic strategy in patients on oral anticoagulants (OAC) who undergoing unplanned percutaneous coronary intervention (PCI). Methods: Using data from the SWEDEHEART registry, we identified all patients on OAC who underwent an unplanned PCI, from 2005 to 2017. We compared uninterrupted OAC (U-OAC) vs interrupted OAC (I-OAC) therapy, defined as any discontinuation of OAC at least 24 hours prior to PCI. Outcomes were major adverse cardiac and cerebrovascular events (MACCE), including death, MI or stroke and net adverse cardiac and cerebrovascular events (NACCE), including MACCE or major bleeds, up to 120 days after the index procedure. Results: We included 6485 patients, 3163 in U-OAC and 3322 in I-OAC group. The U-OAC strategy increased over time, by 13% per year. Almost 80% of patients in both groups had an acute coronary syndrome. We found no major differences in terms of medical history, clinical characteristics and the CRUSADE bleeding score on admission. The proportion of patients on warfarin was higher in the I-OAC group (85 vs 81%). Patients in the I-OAC were more likely to receive low-molecular weight heparin (29 vs 12%) and glycoprotein IIb/IIIa inhibitors (6 vs 3%) during the index hospitalisation. In the I-OAC group, dual antiplatelet therapy without OAC was more often prescribed (22 vs 8%) and OAC plus single antiplatelet therapy was less often prescribed (8 vs 22%) at discharge. At 120 days, the cumulative rate of MACCE was 8.2 vs 8.2% and the rate of NACCE was 12.6 vs 12.9% in I-OAC vs U-OAC, respectively. We found no significant difference in the risk for MACCE and NACCE between the two groups (table). The risk for major or minor in-hospital bleeds was similar. I-OAC was associated with significantly longer time-delay to PCI and length of hospitalisation (table). Conclusion: Uninterrupted OAC was safe and was associated with significantly shorter length of hospitalisation. Our data support U-OAC as the preferable strategy in patients on OAC undergoing PCI. Funding Acknowledgement: Type of funding source: None